1954
DOI: 10.1021/jf60031a005
|View full text |Cite
|
Sign up to set email alerts
|

Alfalfa Carotenoids, Xanthophylls in Fresh and Dehydrated Alfalfa

Abstract: from the technical grade monostearin absorb less moisture than do the products made from the purer or molecularly distilled monostearin.Comparison of Permeability of Films of Acetostearin Products and Other Types of Coating Materials. There apparently are no data in the literature on the permeability of fats and fatlike products to moisture, but data are available for many other organic compounds. To provide a basis for comparing acetostearin products and other organic compounds, some of the literature data ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

1957
1957
1988
1988

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…However, it must be emphasized that different methods of analysis were used for the alfalfa and corn products. Neither method gives an exact measure of the total weight of xanthophylls in the respective products because of the many different xanthophylls present in each product (Bickoff et al, 1954;Quackenbush et al, 1961). The new WRRL procedure slightly underestimates the total weight of xanthophylls in alfalfa by about 10% since the neoxanthin and carotenoid oxidation products (polyoxy fraction) are partly discounted.…”
Section: Discussionmentioning
confidence: 97%
“…However, it must be emphasized that different methods of analysis were used for the alfalfa and corn products. Neither method gives an exact measure of the total weight of xanthophylls in the respective products because of the many different xanthophylls present in each product (Bickoff et al, 1954;Quackenbush et al, 1961). The new WRRL procedure slightly underestimates the total weight of xanthophylls in alfalfa by about 10% since the neoxanthin and carotenoid oxidation products (polyoxy fraction) are partly discounted.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, Bickoff et al (1954) reported that the total amount of violaxanthin and neoxanthin represented over 50% of the total xanthophylls found in fresh alfalfa. However, no significant amounts of these carotenoids were found in the untreated LPC.…”
Section: Discussionmentioning
confidence: 99%
“…A recent extensive xanthophyll analysis of fresh and dehydrated alfalfa meal by Livingston et al (1968) has shown that lutein plus its cis isomers or derivatives comprise a considerably greater portion of the total xanthophylls than reported earlier by Bickoff et al (1954). In the more recent work lutein plus its cis isomers or derivatives comprised 82% of the xanthophylls measured while neoxanthin and violaxanthin amounted to only 18%.…”
Section: Discussionmentioning
confidence: 84%
“…The lutein, neoxanthin and violaxanthin used in this study were isolated from an extract of fresh alfalfa by a procedure similar to that of Bickoff et al (1954). Briefly, the procedure consisted of the preparation of an acetone extract, transfer of the pigments to hexane, and chromatography of the hexane extract on MgO-Celite (1-1).…”
mentioning
confidence: 99%